2023
DOI: 10.1021/acs.jpcb.3c00593
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Binding Behavior of Imidazolium Ionic Liquids to the Receptor Binding Domain of the SARS-CoV-2 Spike Protein

Peng Liu,
Yao Li,
Yawei Liu
et al.

Abstract: The receptor-binding domain (RBD) of the SARS-CoV-2 spike protein is considered as a key target for the design and development of COVID-19 drugs and inhibitors. Due to their unique structure and properties, ionic liquids (ILs) have many special interactions with proteins, showing great potential in biomedicine. Nevertheless, few research studies have been carried out on ILs and the spike RBD protein. Here, we explore the interaction of ILs and the RBD protein through large-scale molecular dynamics simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Binding of the S protein to ACE2 causes conformational changes that led to a transition from a metastable prefusion state to a stable postfusion state . Theoretical studies have attempted to prevent RBD binding by inhibiting ACE2 receptor using different molecules. Our previous studies have shown that plant-based molecules inhibit receptors and several proteins in the pathway by restricting conformational freedom . Currently, symptomatic treatment is the only effective treatment option; therefore, the development of specific targeted drugs is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Binding of the S protein to ACE2 causes conformational changes that led to a transition from a metastable prefusion state to a stable postfusion state . Theoretical studies have attempted to prevent RBD binding by inhibiting ACE2 receptor using different molecules. Our previous studies have shown that plant-based molecules inhibit receptors and several proteins in the pathway by restricting conformational freedom . Currently, symptomatic treatment is the only effective treatment option; therefore, the development of specific targeted drugs is crucial.…”
Section: Introductionmentioning
confidence: 99%